Feasibility Study of a PET Detector with a Wavelength-Shifting Fiber Readout - Anzori Sh. Georgadze (Instruments)
We designed and evaluated the performance of a high-resolution large-area detector for positron emission tomography (PET) based on a crystal assembly readout using wavelength-shifting (WLS) fibers, offering a cost-effective alternative to the direct readout of monolithic crystals with photodetectors. The considered detector geometries were made up of 4 × 4 assemblies of LuY2SiO5:Ce (LYSO) crystal scintillators, each with surface area of 50 × 50 mm2 and thickness of 7 or 15 mm, which were optically coupled together using optical adhesive. The crystal assembly was coupled with square cross-sections of orthogonal wavelength-shifting (WLS) fibers placed on the top and bottom of the assembly. To evaluate the characteristics of the novel detector, we used GEANT4 to perform optical photon transport in the crystal assembly and WLS fibers. The simulation results show that best position resolution achieved was 1.6 ± 0.4 mm full width at half maximum (FWHM) and 4.2 ± 0.6 mm full width at tenth maximum (FWTM) for the crystal thickness of 7 mm and 1.7 ± 0.4 mm FWHM and 6.0 ± 0.6 mm FWTM for the crystal thickness of 15 mm. Compared with a direct photosensor readout, WLS fibers can drastically reduce the number of photosensors required while covering a larger sensitive detection area. In the proposed detector design, 2N photodetectors are used to cover the same image area instead of N2 with a direct readout. This design allows for the development of a compact detector with an expanded effective field of view and reduced cost.